ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SD MELALUI PENERAPAN MODEL PEMBELAJARAN AKTIF PICTURE AND PICTURE - Ristika; Mella Triana (Epsilon: Jurnal Pendidikan Matematika, 2022)
The ability to think creatively is an important ability to be provided to students starting from the elementary school level in the revolutionary era that demands creativity in all things, but this ability has not been fully mastered by elementary school students. This study aims to analyze the creative thinking skills of elementary school students through the application of the Picture and Picture active learning model in the fifth grade of SD Al Azhar 1 Bandar Lampung. The study used an experimental method with the research population of all fifth grade students of SD Al Azhar 1 Bandar Lampung and a sample of 2 classes. The sample was taken using the Cluster Random Sampling technique. The ability to think creatively in mathematics is measured by a test in the form of an essay as many as 4 questions which are first tested for validity and reliability. Hypothesis testing using t-test, obtained t-hitung = 6.92. From the t distribution table at a significant level of 5%, it is known that t-daf = 1.99, which means that t-hit > t-daf is 6.92 > 1.99, so it can be concluded that the mathematical creative thinking ability of fifth graders at SD Al Azhar 1 Bandar Lampung can be influenced through the application of the Picture and Picture active learning model, this can be seen from the average mathematical creative thinking ability of students who apply the Picture and Picture learning model is not the same as the average mathematical creative thinking ability of students who use conventional learning models namely 80.11 and 52.61.